The Afghan - Forsyth, Frederick (London Bantam Press, 2006)
When British and American intelligence catch wind of a major Al Qaeda operation in the works, they are primed for action - but what can they do? They know nothing about the attack: the what, where or when. they have no sources in Al Qaeda, and it's impossible to plant someone. Impossible, unless ... The Afghan is Izmat Khan, a five-year prisoner of Guantanamo Bay and a former senior commander of the Taliban. The Afghan is also Colonel Mike Martin, a 25-year veteran of war-zones around the world, a dark, lean man born and raised in Iraq. In an attempt to stave off disaster, the intelligence agencies will try to do what no one has ever done before - pass off a Westerner as an Arab among Arabs - pass off Martin as the trusted Khan.
Keywords: Islamic fundamentalism